Докирилівський напис на пряслиці з ранньослов’янського поселення Обухів II - Кравченко, Н.М.; Абашина, Н.С. (Археологія, 2001)
Репрезентовано дешифрування напису на пряслиці з поселення Обухів II на Київщині, що ґрунтується на схожості знаків з літерами давньогрецького алфавіту. Исходя из сходства знаков, нанесенных по сырой глине на пряслице из раннеславянского поселения Обухов II с буквами древнегреческого алфавита, авторы предлагают дешифровку надписи как слово «ОУ(Н)ГОЛ». Аналогии можно найти в летописи. Это одно из наименований реки Орель, а также название восточнославянского племени уличей, проживавшего ранее на Днепре, а затем на Южном Буге. На пряслице, вероятно, нанесено имя собственное, имеющее соответствие в племенном наименовании. Starting from the similarity of signs drawn before baking on a spindle-whorl from an early Slavic settlement of Obukhiv II with Greek letters, the authors propose a decoding of the inscription as the word «OU(N)GOL». Analogies can be found in annals. It is one of the names of the Orel’ river and is the name of the Slavic tribe of Ulychi, which lived previously on the Dnieper and then on the Southern Bug. Perhaps, it is a proper noun, which has a correspondence in the tribe name.